Esensi aktivitas-materialitas-karakter pada ruang dan pelingkup arsitektur rumah Osing - Ami Zamzami; Purnama Salura; Yuswadi Saliya (ARTEKS : Jurnal Teknik Arsitektur, 2022)
The phenomenon of a single architectural form has become a global problem. This is also observed in Indonesia as indicated by the specific traditional architecture known as Osing in Banyuwangi. Therefore, this study focuses on the issue of the essence of space created from the surrounding elements in Osing traditional architecture using a qualitative method which involved prioritizing new reading tools including the Lincourt phenomenological approach and the architectural anatomy of Salura. The results showed that the activity forms a linear circular pattern while the lower scoping elements form a geometric arrangement and have a linear movement direction. Moreover, the roof structure shows the dynamic quality of the elements which move from front to back. It was also discovered that the scope of the Osing space is a barrier with the activities within the house isolated and inwardly oriented. The use of local natural materials also provides a warm, rustic and simple character as well as a chance for sustainability. Furthermore, the structures and constructions show that the architecture prioritizes honesty and simplicity. This, therefore, means the essence of space in Osing architecture is in Jrumah based on the space which was found to be closed, natural, simple character, and prioritizing honesty. These findings are expected to be an additional source of knowledge on Osing architecture, serve as input for architects in designing modern houses in Banyuwangi, and input for policymakers in formulating a strategy to preserve this traditional architecture.